2012
DOI: 10.1002/arch.21013
|View full text |Cite
|
Sign up to set email alerts
|

CLONING AND EXPRESSION PATTERN OF HEAT SHOCK PROTEIN GENES FROM THE ENDOPARASITOID WASP, Pteromalus puparum IN RESPONSE TO ENVIRONMENTAL STRESSES

Abstract: Six heat shock protein (HSP) genes from five HSP families in the parasitoid, Pteromalus puparum, were evaluated for their response to temperature (-15 ~ 3°C , and 30 ~ 42°C for 1 h), heavy metals (0.5 ~ 5 mM Cd(2+) and Cu(2+) for 24 h and 60 h), and starvation (24 h). Compared with other insect HSPs, all conserved motifs are found in P. puparum HSPs, and they are very similar to those of the recently sequenced ectoparasitoid Nasonia vitripennis. The temporal gene expression patterns indicated that these six HS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 42 publications
7
42
0
3
Order By: Relevance
“…Recent studies have confirmed that HSP90 has been thought to have evolutionarily conserved functions that contribute to oogenesis and compound eye development in the red flour beetle Tribolium castaneum (Xu et al 2010;Knorr and Vilcinskas 2011). Furthermore, HSP90 messenger(m)RNA or protein have enhanced in response to heat shock (Sonoda et al 2006;Benoit et al 2009;Feng et al 2010;Jiang et al 2012;Wang et al 2012;Li and Du 2013), heavy metal pollution Shu et al 2011;Wang et al 2012), diapause (Tachibana et al 2005), proteotoxic stresses (Jones et al 2008), starvation stresses , and pesticide stresses .…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Recent studies have confirmed that HSP90 has been thought to have evolutionarily conserved functions that contribute to oogenesis and compound eye development in the red flour beetle Tribolium castaneum (Xu et al 2010;Knorr and Vilcinskas 2011). Furthermore, HSP90 messenger(m)RNA or protein have enhanced in response to heat shock (Sonoda et al 2006;Benoit et al 2009;Feng et al 2010;Jiang et al 2012;Wang et al 2012;Li and Du 2013), heavy metal pollution Shu et al 2011;Wang et al 2012), diapause (Tachibana et al 2005), proteotoxic stresses (Jones et al 2008), starvation stresses , and pesticide stresses .…”
Section: Introductionmentioning
confidence: 87%
“…HSP90 is an important gene for arthropods and is used for defense against heat shock Jiang et al 2012;Wang et al 2012;Li and Du 2013) and pesticide stresses . However, little is known about how HSP90 in A. lucorum responds to heat shock and pesticide stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Possibly, HSPs are sufficiently abundant prior to crowding to protect C. terminifera. Starvation induces the expression of genes encoding Hsp20, Hsp60, Hsc70, and Hsp90 in the endoparasitoid wasp, Pteromalus puparum (92); these HSPs are similar to those seen in L. migratoria upon crowding.…”
Section: Starvation and Crowding Induce Insect Hsp Gene Expressionmentioning
confidence: 95%
“…As the synthesis of HSP70s requires considerable energy and may thus occur at the cost of the synthesis of other proteins (Krebs & Loeschcke1994), northern populations might have evolved a less costly way to resist cold stress (Lansing et al 2000;Sørensen et al 2003). HSP70s may not be the only proteins involved in heat and cold resistance; other proteins such as HSP20, HSP60, and HSP90 may also be involved in heat resistance (Zhang & Denlinger 2010;Wang et al 2012) or in the accumulation of low-molecular-weight cryoprotectants (Crowe et al 1988), synthesis of antifreeze proteins (Duman 2001), and remodeling of the structure of the cell membrane (Tomcala et al 2006). Some studies have found HSP70 to be up-regulated 2-5 fold in insects (Colinet et al 2010;Morales et al 2011;Shu et al 2011;Wang et al 2012;Yu et al 2012;Luo et al 2014).…”
Section: Discussionmentioning
confidence: 95%